E - proceeding: 9th Virtual Science Invention Innovation Conference (SIIC) 2020 / Norain Isa - Isa, Norain (2020)
9th Virtual Science, Invention, Innovation & Conference 2020 (SIIC 2020) is organised by Faculty of Chemical Engineering and co -organised by Chemical Engineering Student Society (ChESS) that serves as a platform for final year students from Faculty of Chemical Engineering, UiTM Cawangan Pulau Pinang to highlight idea, innovation, invention and design in their respective field. The event was formerly known as Science, Invention, Innovation & Conference. It has garnered multiple successes following the preceding events from 2016 to 2020. SIIC 2020 showcases products commercialization, ideas, inventions and designs that are highly innovative, competing against each other to be recognized as the best among the best. Adhering to the Industrial Revolution 4.0 movement, the competition seeks out outstanding products that are able to keep up with the rise of automation and artificial intelligent innovations - ideas that can change the way we live, work, and communicate for the better. It is also in line with the government's desire to encourage innovation activities in Malaysia.